Metode Pendidikan Islam Menurut Ahmad Tafsir - WARDI, MOH (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2016)
Islamic education method is the way used to achieve the objectives of Islamic education. According to Ahmad Tafsir view, Islamic education methods that are relevant and effective in Islamic education are drakronis method, synchronous-analytical method, problem solving method, empirical method, deductive and inductive methods. Drakronis is a teaching method that has prominent in history aspect. Synchronous-analytical method is a Islamic education method that provides theoretical analysis capabilities that are very useful for the development of mental faith and intellectual. Problem solving method is a method with approach of the students’ study to find a variety of problems by finding the solution. Empirical method is a method of teaching that allows students to study Islam through the realization and internalization of norms and principles of Islam through an application process which leads to a social interaction. Inductive method conducted by educators by doing a special material to the general conclusion. While Deductive method conducted by educators in the teaching of Islam by showing the general rules and then break them with a variety of examples of problems that become unraveled.